The Living cell - Minnesota Educational Computing Corporation (Minneapolis, MN : MECC, 1991)
A simulation that enables students to increase their knowledge and conceptual understanding of the equilibrium that cells maintain with their environment. Students investigate cell respiration and active transport by assuming the role of the cell membrane--regulating the flow of seven substances into and out of the cell.
Title from title screen.
Ed. statement from disk label.
Stamp on 2nd disk: For archival backup only.
Copy-protected.
Grades 7-12.
Issued also on 3 1/2 in. computer disk.
Keywords: Biological transport -- Regulation -- Software; Biological transport -- Software